2015
DOI: 10.5586/asbp.2015.023
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability of leaves of Sorbus domestica L. in Croatia

Abstract: The paper studies the morphological variability of the service tree populations in the continental and Mediterranean regions of Croatia. The inter-and intra-population variability, as well as eco-geographic population differentiation, was established on the basis of eight measured morphological characteristics of two types of leaflets (lateral and terminal) and two derived ratios, using descriptive and multivariate statistical methods. The conducted research established a high variability of morphological char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
4
16
1
Order By: Relevance
“…This revealed that all traits studied in the lateral leaflet were less diverse (stable) compared to basal and terminal leaflets. Our results are similar to those reported by Brus et al (2011) and Poljak et al (2015) in Sorbus domestica L. For the efficiency of leaflet morphological measurements on compound leaves, we recommend using only lateral leaflet samples.…”
Section: Phenotypic Diversity Among Traits and Populationssupporting
confidence: 90%
See 2 more Smart Citations
“…This revealed that all traits studied in the lateral leaflet were less diverse (stable) compared to basal and terminal leaflets. Our results are similar to those reported by Brus et al (2011) and Poljak et al (2015) in Sorbus domestica L. For the efficiency of leaflet morphological measurements on compound leaves, we recommend using only lateral leaflet samples.…”
Section: Phenotypic Diversity Among Traits and Populationssupporting
confidence: 90%
“…A total of 45 traits were measured on the leaves as shown in Figure 2 and Table 2 following Gonzalez-Rodrigues and Oyama (2005), Brus et al (2011), Jarni et al (2011), and Poljak et al (2015) methods. Leaflet measurements were conducted using a digital caliper with 0.01 mm accuracy of measurements.…”
Section: Measurement Of Morphological Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Left: old tree with broad tree crown growing in the garden (orchard). Right: young tree with the high trunk and absent branches growing in forest is rare in Europe, with the highest frequency of occurrence in the Mediterranean Europe (Balkans, Italy, southern France) and a scattered distribution across Central and Western Europe, extending to Crimea in Ukraine, eastwards, and Northern Africa, southwards (Bignami & Cammilli, 1998;Moinet, 2009;Drvodelić et al, 2015;George et al, 2015;Poljak et al, 2015). It has a two-millennia-long tradition of cultivation in the Mediterranean region dating back to ancient Rome (Brütsch & Rotach, 1993), with the oldest record from Theophrastos (371-287 BC) in ancient Greece (Kausch-Blecken von Schmeling, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Both morphologically and physiologically, dormancy must be broken for germination to occur. Even under optimal conditions (e.g., temperature, light, oxygen, and moisture), some seeds do not germinate due to seed dormancy (Bewley et al, 2013;Poljak et al, 2015). Seed dormancy takes five different forms, namely morpho-physiological dormancy, morphological dormancy, physiological dormancy, physical dormancy, and a combination of physical and physiological dormancy Baskin, 2004, 2014;Bonner, 2008).…”
mentioning
confidence: 99%